Evaluating programming that thinks and works politically: Challenges and emerging practice. Issue 176 (10th February 2023) - Jacobstein, David; Swift, Sarah
Abstract: Issues of power are not new to program evaluation. What is new is a consideration of how programming uses insights into incentives that shape and adapt implementation. How should one evaluate in a way that explicitly assesses the ways in which a program considers power? One of the innovative topics deriving from the democracy and governance space is the approach of thinking and working politically (TWP) which is seeing increased use in development programming. TWP suggests different mental models and practical approaches to achieving development objectives in ways that are more contextually grounded and informed by power dynamics. This article describes several of the core challenges to evaluation of TWP and also a rubric of considerations for more effective evaluation practices in this emerging field.